Synthesis, identification and anticonvulsant activity of dehydrozingerone - M. Awad, Enas; M Ahmed, Elhadi M.; El-hadiyah, Tarig M.; Sirag, Nizar; Abdelrahman, Mohammed (Gezira Journal of Engineering and Applied Sciences, 2019)
The present study aimed to synthesize and characterize dehydrozingerone as well as to investigate its anticonvulsant activity in experimental animals .  A simple method was used to synthesize dehydrozingerone using vanillin and acetone. The synthesized drug dehydrozingerone was characterized using thin layer chromatography (TLC), high performance liquid chromatography (HPLC), infrared spectroscopy (IR) and physicochemical tests.The synthesized product was  tested for its potential anticonvulsant activity using maximum electroshock (MES) induced seizure models in rats. The synthesized dehydrozingerone showed TLC profile, FT IR spectra and HPLC chromatogram similar to the authentic sample. The physicochemical characters (colour, taste, flavour, solubility and melting point) were also similar to what was found in the literature. All these results indicated that the produced product was dehydrozingerone. A dose dependent anticonvulsant activity was produced by dehydrozingerone. Eighty percent anti-MES activity was presented by 100 mg/kg.  The findings indicated that dehydrozingerone represents a bioactive molecule possessing anticonvulsant activity. In addition, it is an easily synthesized compound from cheap starting materials. In conclusion dehydrozingerone may find its place as antiepileptic agent if further clinical studies will be conducted.